2017
DOI: 10.1063/1.5007050
|View full text |Cite
|
Sign up to set email alerts
|

Transient anion spectra of the potential radiosensitizers 5-cyanateuracil and 5-thiocyanateuracil

Abstract: We report on the low energy anion spectra of 5-cyanateuracil (5-OCNU) and 5-thiocyanateouracil (5-SCNU), which have been the suggested potential radiosensitizers for use in cancer therapy [L. Chomicz et al., J. Phys. Chem. Lett. 4, 2853-2857 (2013)]. Employing bound state and scattering calculations, we obtained, for both molecules, a dipole bound state, a π valence bound state, and four π resonances, besides a σ resonance for 5-SCNU. The cyanate and thiocyanate substituents give rise to additional long-lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Based on the above results, a possible dechloridation mechanism of DCE on the oxidized N site was proposed and is shown in Figure d. It has been reported that CH 2 ClCH 2 Cl has a large electron attachment chemistry as great as other halocarbons . Therefore, DCE is absorbed on the surface of the N-doped carbon electrode and attacked by an electron released from the surface of the electrode, forming an excited negative ion * – CH 2 ClCH 2 Cl.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the above results, a possible dechloridation mechanism of DCE on the oxidized N site was proposed and is shown in Figure d. It has been reported that CH 2 ClCH 2 Cl has a large electron attachment chemistry as great as other halocarbons . Therefore, DCE is absorbed on the surface of the N-doped carbon electrode and attacked by an electron released from the surface of the electrode, forming an excited negative ion * – CH 2 ClCH 2 Cl.…”
Section: Resultsmentioning
confidence: 94%
“…H 2 [11]) with increasing level of detail, providing more accurate data than ever before for a number of scattering processes (vibrational and electronic excitation, elastic scattering, etc. ); (ii) bigger targets than ever before (for example, radiosensitizers [12], biomass molecular fragments like lignin [13] and other biomolecules [14]) with a higher level of accuracy; (iii) the effect of the environment by means of the investigation of small molecular clusters. The latter strand of research emerges from the need to understand electron scattering processes beyond the gas phase, for example, in the cell (where low energy electrons are known to play a role in damage produced by ionizing radiation [15]).…”
Section: Introductionmentioning
confidence: 99%
“…As seções de choque de DEA para eliminação de Br − na 5-Br-Uracila (14) sugerem produção eficiente de radicais pela interação com elétrons de baixa energia. Visto que o mecanismo de radiosensibilização de biomoléculas pode estar relacionado com a formação de radicais gerados por DEA com elétrons secundários de baixa energia, estudos vêm sendo realizados com moléculas com potencial radiossensibilizador para melhor entendimento dos mecanismos de sua atividade biológica (12,15,16,17,18,19).…”
Section: Introductionunclassified